OBSTACLE STEPPING and BODY SCALE MODULATING PARAMETERS - Bucken Gobbi, Lilian Teresa [UNESP]; Candido, Rodrigo Pereira [UNESP]; Pinheiro Menuchi, Marcos Rodrigo Trindade [UNESP]; Rozin Kleiner, Ana Francisca [UNESP] (Ammons Scientific, Ltd, 2009)
The purpose of this study was to investigate gait spatial parameters at the point of departure, with obstacle heights adjusted to individual body scale. Undergraduate student volunteers (M age=22.4 yr., SD=2.1; 6 women, 1 man) were asked to step once, then cross over an obstacle and stop. This behavior was video recorded to extract kinematic data. The obstacle heights corresponded to high (knee-height) and low obstacles (half the knee-height). Points of departure corresponded to far (length of the lower limb) and close (half the length of the lower limb). The close point of departure influenced the trailing foot's placement ahead of the obstacle as well as step length. The high obstacle influenced the trailing foot's toe clearance. An interaction between factors was observed for leading foot toe clearance. Results indicate that body scale affected the participants' locomotor behavior during the obstacle-avoidance task.